Outcomes of Salvage Lymph Node Dissection in Oligorecurrent Prostate Cancer Post Radical Prostatectomy: Experience of an Oncologic Center in Spain - Valiquette, Anne S.; Vidal Crespo, Natalia; Wong, Augusto; Mascarós, Juan M.; Gómez-Ferrer, Álvaro; Collado-Serra, Argimiro; Marenco, Jose L.; Casanova Ramón-Borja, Juan; Rubio-Briones, José; Ramirez-Backhaus, Miguel (Frontiers in Urology, 2022)
Introduction and objectives We report our experience with salvage lymph node dissection (sLND) in oligorecurrent prostate cancer (PCa) post radical prostatectomy (RP). Material and Methods We retrospectively analyzed data of 24 patients who underwent sLND for biochemical recurrence (BCR) post RP, from July 2012 to February 2018. sLND was performed following an extended bilateral template. Clinical and pathological characteristics of primary RP and sLND were reported. Biochemical response and initiation of additional therapy post sLND were analyzed. Survival analysis was performed using KaplanMeier curves. Results 24 sLND were performed. RP specimens showed 58.3% of Gleason score 7 and 50% of locally advanced disease. Median time to BCR post RP was 24 months with a median PSA value of 1.4 ng/ml pre sLND. 75% of patients underwent imaging prior to sLND. sLND showed oligometastasis on the final pathology report in 54.2% of patients. Metastatic lymph nodes were mainly identified in the iliac artery territory (61.5%). Complete biochemical response (PSA < 0.2 ng/ml) was maintained throughout the first 12 months of follow-up in 20.83% of patients and 8.33% of patients at the end of the study (median follow-up 70 months). Survival rates free of additional therapy (ADT/RT) were 45.83% at one year and 25% at 5 years. Conclusions We observed a biochemical response post sLND in 20.83% of our patients, lasting throughout the first year of follow up, with survival rates free of ADT and/or RT of 45.83% at one year and 25% at 5 years.